#TITLE_ALTERNATIVE# - ABDUL KADIR (NIM :20512048) ; Pembimbing Dr. Eng. Yessi Permana, Dr. Muhamad A. Martoprawiro, LAODE
Synthesis of glycerol carbonate (4-hydroxymethyl-1,3-dioxolane-2-one) from glycerol and urea using zinc alkoxide (zinc di(sec-butoxide)) as a catalyst has been investigated. The catalyst was prepared from a reaction of zinc chloride with aluminium tri(sec-butoxide) at room temperature for 24 h in dry tetrahydrofuran (THF). Glycerol carbonate was produced from a reaction of glycerol and urea at 150 oC for 4 h. Zinc alkoxide showed good catalytic results when it was employed as the catalyst with mol ratio to glycerol of 1:1000 until 1:20. The highest glycerol conversion of 75% was achieved when mol ratio of catalyst was 1:20. The product was characterized by fourier transform infrared (FT IR), nuclear magnetic resonance (1H NMR) and gas chromatography (GC). Changes in urea carbonyl vibration from 1643 cm-1 to vibrations of the carbonyl group (CO ester) at 1786 cm-1 indicates that glycerol carbonate has been formed. 1H NMR characterization also confirmed that glycerol carbonate has been produced, indicated by the chemical shift in the range of 3.6 to 4.8 ppm. The characterization results of gas chromatography (GC) showed the presence of residual glycerol that was not completely reacted and the presence of a new product. Theoretical study based on computational calculations were also performed in this study. Natural Bond Orbital calculations (NBO) showed that the acidity value of the zinc di(sec-butoxide) was higher than zinc chloride and zinc glycerolate. Furthermore, computational results showed that formation of glycerol carbonate was energetically more dominant than formation of by-product of glycerol carbamates.